Answer:
32
Step-by-step explanation:
brainliest?
Set all the factors equal to 0 and solve for x.
1) x + 6 = 0
x = -6
2) x + 8 = 0
x = -8
3) x + 15 = 0
x = -15
When the function is graphed, you can see that the function crosses the numbers -15, -8, and -6 on the x-axis. These are the zeros.
Answer:
i put 2
Step-by-step explanation:
Answer:
Below
Step-by-step explanation:
Substituting the given values:
f(6) = 6(2/3) - 2 = cube root of 6^2 - 2 = cube root 36 - 2
f(-6)= (-6)(2/3) - 2 = cube root of(-6)^2 - 2 = cube root 36 - 2
So This is true,
f(6) = cube root of 6^2 - 2 = cube root 36 - 2 = 1.3019
2 * f(3) = 2 * (cube root of 3^2 - 2 ) = 2 * (cube root of 9 - 2) = 0.1602
So False,